A Comparative Account on Prevalence of Liver Fluke Metacercariae in Different Larval Stages of Anopheles Stephensi and Aedes Aegypti Larvae at Varying Temperature, Light Intensities and Altering PH in Laboratory Conditions - Vishwas, Vijay (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In present exercise mass level rearing of cercariae of liver fluke and mosquito larvae of two representative species viz. An. stephensi and Ae. aegypti was done in laboratory to set up an experiment for the purpose of estimation of prevalence of metacercariae in different stages of mosquito larvae, which may cause their death. Metacercariae prevalence was observed on different ecological parameters viz. temperature, light and pH value and it was noted that metacercariae prevalence may act as prominent biological control tool for mosquito larvae. Both representative species i.e. An.stephensi & Ae.aegypti were found affected with metacercariae up to remarkable level which may also cause death of mosquito larvae.
Keywords: Anopheles stephensi; Anopheles aegypti; Biological control of mosquito; cercariae; effect of temperature on metacercariae prevalence in mosquito larvae; metacercariae; metacercariae prevalance